The Effect of Tai Chi on College Students’ Stress and Sleep Quality - Chen, Fei; Wang, Xiaodong; Wei, Qiuyang (The Journal of the International Society of Chinese Health Practices, 2025)
Abstract: Psychological stress among college students is becoming increasingly prominent, and its adverse effects are often directly reflected in sleep quality. This creates a vicious cycle in which stress and sleep disturbances exacerbate each other, severely compromising students’ physical and mental health as well as academic performance. Tai Chi, a traditional Chinese mind-body exercise that integrates physical movement with mental focus, is characterized by its gentle, safe, and accessible nature. It is widely recognized as an effective practice for health promotion. However, existing research has primarily focused on elderly or clinical populations, making its findings difficult to generalize to college students. Systematic studies targeting this demographic remain scarce, which limits the effective implementation of Tai Chi in university health promotion programs. Objective: This study aims to investigate the effects of Tai Chi on stress levels and sleep quality among college students, providing rigorous empirical evidence to support the integration of effective mind-body interventions in higher education settings. Methods: A total of 82college students (49 males, 33 females) were recruited and randomly assigned to either an experimental group or a control group. The experimental group received a 12-week Tai Chi (16-form) intervention, consisting of three 90-minute sessions per week. Each session included 30 minutes of conventional warm-up (joint mobility exercises and aerobic running) followed by 60 minutes of Tai Chi practice. The control group maintained their usual lifestyle without any targeted physical intervention. All participants were assessed using the Perceived Stress Scale (PSS) and the Pittsburgh Sleep Quality Index (PSQI) before and after the intervention. Data were analyzed using SPSS 27.0. Results: 1) Effects on Perceived Stress:After the 12-week intervention, the experimental group showed a significant decrease in PSS scores (mean difference = 3.15, t = 5.458, p < 0.001), whereas the control group exhibited a significant increase (mean difference = -6.15, t = -7.427, p < 0.001). Post-intervention, the experimental group’s PSS score (32.55 ± 5.57) was significantly lower than that of the control group (41.45 ± 5.08), with a statistically significant between-group difference (t = -5.279, p < 0.001). 2) Effects on Sleep Quality: The experimental group demonstrated a significant reduction in PSQI scores (mean difference = 0.65, t = 3.577, p = 0.002), while the control group showed a significant increase (mean difference = -1.40, t = -9.200, p < 0.001). After the intervention, the experimental group’s PSQI score (6.30 ± 1.17) was significantly lower than that of the control group (7.80 ± 1.24), with a statistically significant intergroup difference (t = -3.929, p < 0.001). Conclusion: This 12-week randomized controlled trial systematically evaluated the effects of Tai Chi on stress and sleep quality in college students. Key findings include: 1) Tai Chi significantly reduced perceived stress levels. The increase in PSS scores observed in the control group suggests that stress levels in this population may naturally rise due to academic cycles and exam pressures. Tai Chi effectively counteracted this trend, demonstrating positive stress-buffering effects. 2) Tai Chi led to marked improvements in sleep quality. Significant enhancements in the experimental group’s total PSQI score and multiple subcomponents indicate that Tai Chi not only alleviates stress to indirectly improve sleep but may also directly enhance sleep quality through mechanisms such as autonomic nervous system regulation and physical relaxation. In summary, this study confirms that Tai Chi is an effective mind-body intervention for reducing stress and improving sleep quality among college students, supporting its promotion and application in higher education contexts.